Targeting maternal gut microbiome to improve mental health outcomes—a pilot feasibility trial - Gallant, Faith; Cooley, Kieran; Grigoriadis, Sophie; Ebrahimi, Neda (Frontiers in Psychiatry, 2024)
Background Perinatal depression and anxiety (PDA) is prevalent in new and expectant mothers, affecting millions of women worldwide. Those with a history of mood and anxiety disorders are at the greatest risk of experiencing PDA in a subsequent pregnancy. Current safety concerns with pharmacological treatments have led to a greater need for adjunctive treatment options for PDA. Changes in the composition of the microbiome have been associated with various diseases during pregnancy, and these changes are thought to play some role in perinatal mood disorders. While the relationship between PDA and the microbiome has not been explored, evidence suggests that nutritional interventions with fiber, fish oils, and probiotics may play a favorable role in neuropsychiatric outcomes during and after pregnancy. The primary objective of the present study is to assess the feasibility and acceptability of a combination of nonpharmacological interventions to maintain stability in pregnant women who have a history of depression and/or anxiety. This study will also aim to understand ease of recruitment and protocol adherence in this cohort. Methods This is a single-centered, partially randomized, placebo-controlled, double-blind feasibility trial. One hundred pregnant women with a history of depression and/or anxiety/PDA will be recruited and randomized into one of four arms, which could include the following: receiving a daily dose of both investigational products and dietary counseling on increasing dietary fiber, receiving a daily dose of both investigational drugs only, receiving fish oil investigational product and placebo, and a control arm with no intervention. The study involves six study visits, all of which can be conducted virtually every 3 months from the time of enrollment. At all study visits, information on diet, mental health, physical activity, and sleep quality will be collected. Additionally, all participants will provide a stool sample at each visit. Discussion It is anticipated that pregnant women with a history of depression and anxiety will be particularly interested in partaking in this trial, resulting in favorable recruitment rates. Given the positive findings of omega-3 fatty acids (O3FAs) and probiotic supplements on mental health symptoms in nonpregnant adults, we expect a similar trend in PDA symptoms, with a low likelihood of adverse events. This study will build the foundation for larger powered studies to further contribute evidence for the efficacy of this potential preventative treatment option. Trial registration This trial was registered at ClinicalTrials/gov on October 6, 2023; NCT06074250. Trial Sponsor: The Canadian College of Naturopathic Medicine, 1255 Sheppard Ave E, Toronto, ON M2K 1E2, 416-498-1255.